Epigenetic activation of CD274/PD-L1 by the MSL complex expands its role beyond dosage compensation - Wen, Aiping; Feng, Xuanfei; Li, Yingying; Cui, Xueli; Zou, Qixian; Cai, Yong; Jin, Jingji; He, Yunxiao (Frontiers in Immunology, 2025)
IntroductionThe regulation of CD274 (PD-L1), a pivotal immune checkpoint in cancer immunotherapy, remain incompletely understood. The male-specific lethal (MSL) complex, initially identified in Drosophila dosage compensation, contains the core subunit KAT8 (MOF), which catalyzes histone H4 lysine 16 acetylation (H4K16ac). However, whether the MSL complex directly regulates CD274 transcription has not been established.MethodsUsing TIMER and GEPIA2, we charted pan-cancer expression of MSL subunits and their correlation with immune infiltration, integrating Kaplan–Meier survival and copy number variation (CNV) data to assess clinical relevance. CRISPR–Cas9 deletion of MSL1 or MSL3 in HEK293T cells, followed by RNA-seq, identified CD274 as a potential target. MSL1 knockdown or overexpression in LNCaP, HCT116, HeLa and MCF-7 cells confirmed regulation of CD274 protein, validated by rescue experiments in HEK293T cells. Luciferase reporter, ChIP–qPCR and ChIP–seq analyses collectively map the MSL-complex–CD274 regulatory axis.Results and discussionHere we demonstrate that MSL1, a key subunit of the complex directly activates CD274 transcription by recruiting MOF to its promoter region and promoting H4K16 acetylation. Bioinformatic analyses revealed strong correlations between MSL1 expression, immune cell infiltration, and enrichment of immune-related gene sets across multiple cancer types. CRISPR/Cas9-mediated knockout of MSL1 or MSL3 markedly suppressed CD274 expression, whereas MSL1 overexpression enhanced CD274 levels and upregulated downstream immune- and apoptosis-related genes, including BIRC3 and HLA-A. Dual-luciferase reporter assays, ChIP-qPCR and ChIP-seq further confirmed MSL1 binding near the –700 bp region of the CD274 promoter. Collectively, these findings uncover a previously unrecognized epigenetic mechanism linking the MSL complex to CD274 transcriptional regulation and identify MSL1 as a potential target for enhancing immunotherapy efficacy.